Interaction of non-profit organizations and state structures of the region in the field of adaptive physical culture - Strizhakova, E.V.; Kadutskaya, L.A.; Shimokhina, M.V.; Arakelyan, D.G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify trends in the development of interaction between government agencies and non- profit organizations whose activities are aimed at working with people with various health disorders. Methods and structure of the study. In the course of the work, a survey and analytical methods were used: data from open sources on the research problem, official state statistics were analyzed, a content analysis of the content of official sites, regulatory legal documents on the organization of extrabudgetary activities was carried out. Results and conclusions. The features of the provision of services by state organizations, non-profit organizations within the framework of project activities and grant support in the field of adaptive physical culture and sports are revealed. Based on the results of the analysis of the involvement of non-profit organizations (NPOs) and socially oriented non-profit organizations (SO NPOs) in the scheme of interaction with government agencies, their effectiveness in providing services (works) to the population in the field of adaptive physical culture and sports, a scheme of interaction was developed and proposed to solve the identified problems.